TRANSFORMATIONAL LEADERSHIP IN THE IMPLEMENTATION OF BILINGUAL LEARNING AT MIN 2 JEPARA: A QUALITATIVE CASE STUDY - Arina Arina; Subaidi Subaidi; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study analyses the role of transformational leadership in implementing bilingual learning within the framework of the Merdeka Curriculum at Madrasah Ibtidaiyah Negeri (MIN) 2 Jepara, a state Islamic primary school in rural Central Java. The research addresses how a madrasah principal mobilises leadership to sustain an English-medium bilingual programme that integrates global competence with Islamic values amid constrained linguistic and material resources. A qualitative single-case study design was employed, drawing on semi-structured interviews with five key informants (the principal, the bilingual-class coordinator, the vice-principal for curriculum, and bilingual teachers), participant observation in bilingual classrooms, and document analysis. Data were examined through thematic analysis and triangulated across sources. The findings indicate that the principal’s transformational leadership, operating through idealised influence, inspirational motivation, intellectual stimulation, and individualised consideration, functioned as the decisive mechanism converting a policy aspiration into a working classroom practice. Leadership effects were realised indirectly, mediated by teacher capacity built through continuous in-house training, professional learning communities, and technology-enabled pedagogy, rather than through structural mandate. The principal reframed limited English proficiency among teachers and students from a deficit into a shared developmental project, while embedding Islamic values into English instruction through practices such as English Morning and value-laden vocabulary, producing synergy rather than dichotomy between globalisation and religious identity. The study contributes a religio-cultural, rural extension to transformational-leadership theory and offers transferable strategies for resource-limited madrasahs. The single-site design limits statistical generalisation but supports analytical generalisation to comparable Islamic schools.